A temporal profile of pro-abstinence-oriented constructs from the modified theory of planed behavior in a Slovenian clinical sample of treated alcoholics - an 18-year follow-up - Radovanovič, Mirjana (Zdravstveno varstvo, 2018)
Introduction: Using the modified Theory of Planned Behaviour (mTPB), different indicators of therapeutic success were studied to understand pro-abstinence behavioural orientation during an 18-year after-care period following a 3-month intensive alcoholism treatment. The indicators were: perceived needs satisfaction (NS), normative differential (ND), perceived alcohol utility (UT), beliefs about treatment programme benefits (BE) and behavioural intentions (BI). Methods: The sample of 167 patients who consecutively started an intensive alcoholism treatment programme has been followed-up for 18 years, using standardised ailed instruments at the end of the treatment, and in the years 4-5, 9 and 18 of follow-up. The last data collection was completed by 32 subjects in 2010. The analysis followed the standard explore-analyse-explore approach. After the initial descriptive exploration of data, multivariate analysis of variance (MANOVA) in SPSS statistical package was set to explore between-groups and within-groups differences over time. Results: At the between-group level, BI remained stable at the same level as at the end of the treatment programme, whereas BE and UT robustly changed over time and levelled off after 10 years of follow-up. NS and ND show a trend of pro-abstinent orientation and level off after 10 years of follow-up, although the trend is not significant. The same results were confirmed by the within-subject level. Conclusions: Studied constructs stabilised after ten years of follow-up, apart from BI. The latter suggests that BI level needed for completion of an intensive treatment programme suffices for the maintenance of abstinence when accompanied by the change in perception of alcohol usefulness.
Keywords: alcoholism treatment; behavioral indicator; dolgoročna abstinenca; kazalniki vedenja; long-term abstinence; program zdravljenja sindroma odvisnosti od alkohola; teorija načrtovanega vedenja; theory of planned behaviour